A descriptive literature review of Recognition of Prior Learning for vocational learners in emergency medical care in South Africa - Winstanley, D.; Cunningham, C. (South African Journal of Higher Education, 2023)
Radical advances in emergency medical care education in South Africa have resulted in both advancements and suppression. After short-course vocational training, the emergency care provider could seek employment in an emergency service. With the realignment of emergency medical care programmes to the National Qualifications Framework (NQF), these short vocational courses were phased out by 2018. Although necessary for educational advancement, these changes prevented vocationally trained emergency care providers from articulating into higher education without returning to full-time academia. Moreover, despite recognition of prior learning (RPL) policies in higher education, few institutes offering emergency medical care programmes offered this as an access option. This descriptive literature review aimed to analyse the RPL processes in South Africa and globally. Additionally, insight into RPL candidates” support requirements for postgraduate studies was gained. A systematic search of peer-reviewed journal articles, periodicals, dissertations, and governmental reports from 2000 to 2021 was conducted. Various databases were accessed, including Proquest, EBSCOhost, LearnTechLib, JSTOR, ERIC, Google Scholar, and the Thesis Repository. The lack of literature focusing on the prehospital RPL system in South Africa prompted search expansions into the field of health science internationally. Of the 401 screened sources, 19 met the researcher’s inclusion criteria. Two additional articles were sourced in a repeated search in February 2022. The findings revealed enablers and barriers for RPL students and expanded on their personal and academic transitions. The themes identified through the enablers and barriers can assist in identifying additional support for RPL students during their educational journey. Ultimately, despite vital institutional transitions in RPL processes, intrinsic motivation inspired these students to embrace the challenges they faced, and their process of personal transition and lifelong learning began.